EVALUASI,DAMPAK PENERAPAN KEBIJAKAN PERATURAN,,WALIKOTA, NOMOR 3 ,TAHUN 2014 TENTANG,,PENYELENGGARAAN, REKLAME, TERHADAP PEMUNGUTAN PAJAK REKLAME, DI, BADAN PENDAPATAN DAERAH KOTA, DENPASAR - Wulandari, I Dewa Ayu; Yasintha, Putu Nomy; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2021)
This study aims to determine, the impact evaluation of,the implementation of Mayor Regulation Number 3 of 2014, on the Implementation of Advertising, on Advertisement Tax Collectors at the Regional Revenue Agency of Denpasar City.,The research, methodin this research is a qualitative descriptive with data sources through observation and interview techniques for informants. The theory, used, by researcher is William Dun’s policy evaluation theory using indicators of ,effectiveness, efficiency, responsiveness, and ,accuracy. It was found that the ,collection of advertisement tax in Denpasar City which was carried out by the Denpasar City government was still not doing optimal, because there were still many obstacles and violators in the implementation of billboards, both unpreparedness from the government agencies and stakeholders in the installation of billboards. Keywords: Local Government, Advertising, Local Tax, Advertising Tax